Pre-existing opioid use disorder and postoperative outcomes after appendectomy or cholecystectomy: A multi-state analysis, 2007-2014 - Boltunova, MD, Alina; White, MD, MS, Robert S.; Noori, MD, Selaiman; Chen, BA, Stephanie A.; Gaber-Baylis, BA, Licia K.; Weinberg, MD, Roniel (Journal of Opioid Management, 2019)
Introduction and objectives: Opioid use disorder has become increasingly prevalent in recent years. Previous studies have shown that patients with opioid use disorder undergoing orthopedic, elective abdominopelvic, and cardiac procedures have poorer postoperative outcomes. The aim of this study was to examine the effect of pre-existing opioid use disorder on postoperative outcomes including in-hospital mortality, hospital length of stay (LOS), hospital readmission, and postoperative complications in patients undergoing appendectomy or cholecystectomy. Methods: The authors used administrative data from the State Inpatient Databases of the Healthcare Cost and Utilization Project for the years 2007-2014 from California, Florida, Kentucky, Maryland, and New York. The authors compared unadjusted rates of in-hospital mortality, postoperative complications, LOS, and 30-day and 90-day readmission status. The authors calculated the adjusted odds ratio (OR) for their outcomes using logistic regression models. Results: In all, 488,981 appendectomy patients and 790,491 cholecystectomy patients aged ≥ 18 years were included in the analysis. Appendectomy (OR 2.26) but not cholecystectomy patients with opioid use disorder had statistically significant adjusted odds of in-hospital death. Patients with opioid use disorder (overall reported, and by each procedure separately) had higher adjusted odds of postoperative complication (OR 1.46), 30-day readmission (OR 1.80), 90-day readmission (OR 1.98), and longer LOS (OR 1.37). Conclusions: The authors found higher unadjusted rates and adjusted ORs of in-patient mortality, hospital readmission, and postoperative complications in patients with opioid use disorder undergoing common abdominal surgeries. The authors’ study shows that opioid use disorder is a risk factor for poorer postoperative outcomes in this surgical patient population.